Gluing Living Bone Using a Biomimetic Bioadhesive: From Initial Cut to Final Healing - Procter, Philip; Hulsart-Billström, Gry; Alves, Antoine; Pujari-Palmer, Michael; Wenner, David; Insley, Gerard; Engqvist, Håkan; Larsson, Sune (Frontiers in Bioengineering and Biotechnology, 2021)
Osteoporotic fractures are a growing issue due to the increasing incidence of osteoporosis worldwide. High reoperation rates in osteoporotic fractures call for investigation into new methods in improving fixation of osteoporotic bones. In the present study, the strength of a recently developed bone bioadhesive, OsStictm, was evaluated in vivo using a novel bone core assay in a murine animal model at 0, 3, 7, 14, 28, and 42 days. Histology and micro-CT were obtained at all time points, and the mean peak pull-out force was assessed on days 0–28. The adhesive provided immediate fixation to the bone core. The mean peak bone core pull-out force gradually decreased from 6.09 N (σ 1.77 N) at day 0 to a minimum of 3.09 N (σ 1.08 N) at day 7, recovering to 6.37 N (σ 4.18 N) by day 28. The corresponding fibrin (Tisseel) control mean peak bone core pull-out characteristic was 0.27 N (σ 0.27 N) at day 0, with an abrupt increase from 0.37 N (σ 0.28) at day 3, 6.39 N (σ 5.09 N) at day 7, and continuing to increase to 11.34 N (σ 6.5 N) by day 28. The bone cores failed either through core pull-out or by the cancellous part of the core fracturing. Overall, the adhesive does not interrupt healing with pathological changes or rapid resorption. Initially, the adhesive bonded the bone core to the femur, and over time, the adhesive was replaced by a vascularised bone of equivalent quality and quantity to the original bone. At the 42 day time point, 70% of the adhesive in the cancellous compartment and 50% in the cortical compartment had been replaced. The adhesive outwith the bone shell was metabolized by cells that are only removing the material excess with no ectopic bone formation. It is concluded that the adhesive is not a physical and biochemical barrier as the bone heals through the adhesive and is replaced by a normal bone tissue. This adhesive composition meets many of the clinical unmet needs expressed in the literature, and may, after further preclinical assessments, have potential in the repair of bone and osteochondral fragments.